Ministry of Health and Population Decree No. 5 of the year 2017 Concerning the Rules for Importing Drugs, Raw Materials, Biologicals, Formula Milk and Medical Supplies from Reference and Non-Reference Countries = وزارة الصحة والسكان قرار رقم 5 لسنة 2017 بشأن قواعد استيراد الأدوية والخامات والمستحضرات الحيوية وألبان الأطفال والمستلزمات الطبية من الدول المرجعية وغير المرجعية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic